A House Divided? Examining Persistence for On-Campus STEM and Non-STEM Students. (August 2017) - Gansemer-Topf, Ann M.; Kollasch, Aurelia; Sun, Jie
Improving student persistence, especially in science, technology, engineering, and mathematics (STEM) fields, continues to be at the forefront of national educational policy discussions. Living in university housing, with its focus specifically on assisting students in transition, has consistently been positively related to student persistence. Using institutional data and data from a first-year student transition study from all the first-year first-time residential students from Fall 2008 through Fall 2012 ( N = 17, 850), this study examined the relationship between student characteristics and experiences and retention for STEM and non-STEM students who live in on-campus housing. Results illustrate that experiences that contribute to retention differ between STEM and non-STEM students. Noncognitive factors related to academic self-efficacy, academic adjustment, and degree aspiration positively affect residential students' persistence in STEM. Academic performance was a significant factor in institutional persistence for STEM and non-STEM students. Implications for future and practice are discussed.